(untitled) (Research, Society and Development, 2021)
Objective: Analyze the knowledge of the puerperal in domestic emergency situations involving infants. Methodology: Exploratory field study with quantitative approach that will be held at in in the month of May 2021 university hospital located in the city of Rio de Janeiro. The data collection was through anonymous questionnaires, with closed structured questions, self-filled by the puerperal. Results: From this research, it was found that 83% of the mothers interviewed were not received during prenatal consultations, some teaching about first aid to infants by the health professional who assisted them. In addition to this highlighted point, it is noteworthy that 100% of respondents would like to receive information from health professionals on how to provide assistance to babies. Conclusion: If pregnant and puerperal had, during prenatal and postnatal appointments, some teaching or guidence by the health professional on how to act on emergency situations with the baby, the problems would be easier to diagnose, because the mothers would know how to identify what the child has and would know how to provide an assertive care to increase the victim’s survival. The interviewees showed interest in receiving information’s from health professionals on how to provide aid to babies.